Too few university graduates. Inclusiveness and effectiveness of the Italian higher education system. (September 2020) - Contini, Dalit; Salza, Guido
Abstract: Despite the absence of formal entry barriers, Italy is lagging behind the majority of the developed countries in the share of young individuals with tertiary education. Exploiting the administrative data of a large public Italian institution, we analyze student academic careers across recent matriculation cohorts. We propose a flexible discrete-time competing risks estimation that allows overcoming some major limitations of conventional competing risks models. We find that student pathways vary tremendously across prior schooling profiles: for example, the within 4-year dropout probability ranges between 10% and 77%. We observe improvements over time in retention and time-to-degree, and by decomposing changes into components related to the composition of the enrolled population, the choice of the field of study and 'individual behavior' after enrolment, we find that the latter plays a major role. However, the improvement is limited in size and does not interest students from the vocational track. Since this progress is not accompanied by an increase in the share of students making the transition from high school to university, altogether our results call for great concern over the inclusiveness and effectiveness of the Italian university system. Highlights: Despite formal openness of the educational system, Italy has a very low share of young individuals with tertiary education. We find huge differences in student pathways across prior schooling but overall improvement in retention and time-to-degree · Compositional effects exist but are not the major driver of the changes. . Differently from the others, students from the vocational track do not experience a reduction in the dropout risk The evidence is that the Italian university system is becoming more effective but not more inclusive.